إمكانية تطوير نظم المعلومات المحاسبية في المصارف من خلال استخدام وسائل تقنيات المعلومات الحديثة بالتطبيق على مصرف الرافدين /نينوى-112 - زياد هاشم يحيى; اخلاص هزاع العبدلي (PROSPECTIVE RESEARCHES, 2023)
The research devoted the concept of information technology (IT) and the devices which can use in the banks. Through the analytical study for accounting information system (AIS) in the Al- Rafidan Bank Nineveh Branch 112 and evaluation the devices of information technology that using in it, the research game out of suggestion to added some of other types that will be contributing in performance the bank work and then to developing accounting information system so as to increase its efficient and effectiveness.